2017
DOI: 10.1155/2017/4578973
|View full text |Cite
|
Sign up to set email alerts
|

Poor Sleep Quality Is Associated with Dawn Phenomenon and Impaired Circadian Clock Gene Expression in Subjects with Type 2 Diabetes Mellitus

Abstract: Aims. We investigated whether poor sleep quality is associated with both dawn phenomenon and impaired circadian clock gene expression in subjects with diabetes. Methods. 81 subjects with diabetes on continuous glucose monitoring were divided into two groups according to the Pittsburgh Sleep Quality Index. The magnitude of dawn phenomenon was quantified by its increment from nocturnal nadir to prebreakfast. Peripheral leucocytes were sampled from 81 subjects with diabetes and 28 normal controls at 09:00. Transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Similarly, the combined downregulation in the expressions of CRY1 and PER3 at midnight predicted the severity of the disease in patients with obstructive sleep apnea/hypopnea syndrome [18]. Additionally, in patients with type 2 diabetes, those with the poorest sleep quality showed a dampened mRNA expression of clock genes such as BMAL1 and PER1 [33]. Therefore, we propose that the disorder in nocturnal breathing that characterize the sleep of patients with type 2 diabetes could alter the circadian rhythm (Figure 3).…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, the combined downregulation in the expressions of CRY1 and PER3 at midnight predicted the severity of the disease in patients with obstructive sleep apnea/hypopnea syndrome [18]. Additionally, in patients with type 2 diabetes, those with the poorest sleep quality showed a dampened mRNA expression of clock genes such as BMAL1 and PER1 [33]. Therefore, we propose that the disorder in nocturnal breathing that characterize the sleep of patients with type 2 diabetes could alter the circadian rhythm (Figure 3).…”
Section: Discussionmentioning
confidence: 95%
“…There is a certain similarity between the dawn phenomenon and the dusk phenomenon in clinical characteristics, from which we may get some enlightenment. The mechanism of the dawn phenomenon is complex and diverse: the loss of β cell function, [ 20 ] growth hormone-induced insulin resistance, [ 21 ] increasing of circulating insulin-like growth factor binding protein-1 in the morning, [ 22 ] poor sleep quality, and the impairment of circadian clock [ 23 ] seemed to be closely involved in the pathophysiology of dawn phenomenon in people with diabetes. However, the correlation and regression analysis showed no relationship between the dawn phenomenon and the dusk phenomenon in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, studies have shown that circadian clock genes were associated with sleep outcomes in human research 13 . Thus, the essential question we addressed in our study was whether sleep quality and circadian rhythm genes expression were altered upon thyroid nodule patients, especially malignant nodules; whether poor sleep quality was the risk factor associated with thyroid malignancies; and whether there was a correlation between sleep disorders and circadian rhythm genes, which may be involved in the development of thyroid malignancy.…”
Section: Introductionmentioning
confidence: 99%